Vehicles Routing Using Composite Approach For Small Businesses - Chartniyom, Siradej (Srinakharinwirot University Engineering Journal, 2020)
This article presents the capacitated vehicle routing problem that associated with the limit of vehicle capacity. The problem represents a type of actual daily delivery under constraints of maximun of 30 locations and the demand over the locations occurs randomly. The model aims to solve for minimum routing target using the designed solution procedure based on the composite approach, and applies the current transportation management system along with spreadsheet solvers. The proposed solution procedure allows the company to deal easily with actual transportation routes and distances in their daily scheduling tasks. The result of the study shows that a metaheuristic method, within the spreadsheet solver, gives the best performance. The set of sample schedules returns the reduction of 8% in the total transportation cost.